Active energy ray-curable composition and resin molding
The solvent-free active energy ray curing composition, featuring multifunctional acrylates and intramolecular cleavage initiators, addresses viscosity issues and enhances recyclability, resulting in improved adhesion and reduced waste.
Patent Information
- Application Number
- JP2023151738
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-19
- Publication Date
- 2025-04-01
AI Technical Summary
Existing active energy ray curable compositions face issues with viscosity changes during storage, leading to inefficiencies in reuse and increased waste when not fully adhered to substrates.
A solvent-free active energy ray curing composition is developed, containing multifunctional acrylates and intramolecular cleavage initiators, with a viscosity of 10 to 60 mPa·s and a viscosity change rate of ±20% or less, allowing for efficient reuse of uncoated kimono.
The composition achieves improved adhesion, reduced waste, and enhanced recyclability, with a cured film that maintains durability even in low-temperature environments.
Smart Images

Figure 2025044051000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an active energy ray-curable composition and a resin molded article. [Background technology]
[0002] Transparent synthetic resins such as polycarbonate resin (PC) and polymethyl methacrylate resin (PMMA) are excellent in transparency, moldability, and mechanical properties, and are therefore used in many fields, such as covers (outer covers) for lamps of automobiles and motorcycles, lenses for glasses, covers for optical sensors, and various liquid crystal panels. However, on the surface of a molded product such as a synthetic resin, when the surface temperature falls below the dew point temperature, moisture in the air condenses into fine droplets, causing fogging. This reduces light transmittance, leading to poor visibility and malfunction of sensors, etc. There is also a problem that scratches or dirt adhere to the surface of a molded product such as a synthetic resin, reducing light transmittance, leading to poor visibility and malfunction of sensors, etc. In order to prevent such problems, a composition is applied to the surface of a molded product (coated product) such as a synthetic resin, and the composition hardens on the surface of the molded product as a cured film, thereby ensuring transparency.
[0003] However, when the composition is sprayed onto the surface of a molded article, the composition that does not adhere to the surface of the molded article, i.e., the uncoated portion, is discarded, which results in poor utilization of the composition, and causes problems such as increased costs and increased environmental load.
[0004] For example, Patent Document 1 discloses a method and device for recovering UV-curable paint that recovers UV-curable paint that has not adhered to an object to be coated. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2005-342550 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, even if the composition that has become the object to be coated is recovered in this manner, if the viscosity of the object to be coated has increased, the composition that has become the object to be coated cannot be used again for spray coating.
[0007] The present invention has been made in consideration of the above-mentioned points, and an object of the present invention is to provide a reusable active energy ray-curable composition and a resin molded article having a cured film obtained by curing the active energy ray-curable composition. [Means for solving the problem]
[0008] A solventless active energy ray-curable composition containing a multifunctional acrylate and an intramolecular cleavage initiator, wherein the active energy ray-curable composition has a viscosity of 10 to 60 mPa s and exhibits a viscosity change rate of ±20% or less before and after storage for 30 minutes in the presence of a fluorescent lamp and in an air atmosphere at a temperature of 23°C. [Brief description of the drawings]
[0009] [Figure 1] 1 is a conceptual diagram showing a resin molded article of the present invention. [Diagram 2] 1A to 1C are diagrams illustrating a manufacturing process of a resin molded article according to the present invention. [Diagram 3] 1 is a table summarizing the results of comparison between Examples and Comparative Examples of the active energy ray-curable composition of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] An embodiment of the present invention will be described. The active energy ray curable composition 10 of the present invention is a solventless type. Here, "solventless type" means that the active energy ray curable composition 10 does not contain a non-reactive volatile organic solvent, or does not substantially contain a non-reactive volatile organic solvent. "Substantially does not contain a non-reactive volatile organic solvent" means that the active energy ray curable composition is subjected to gas chromatography analysis at 200°C, and the total value of components detected as structures not containing a vinyl group or an acryloyl group is less than 1 mass%.
[0011] Since the active energy ray curable composition 10 is a solvent-free type, when the active energy ray curable composition is cured, most of it becomes a cured film as an active ingredient. Therefore, the total amount of the active energy ray curable composition required for coating on the surface of the substrate 20 (molded product) can be reduced.
[0012] The active energy ray-curable composition 10 has a viscosity change rate (%) of ±20% or less before and after storage for a predetermined time under predetermined conditions. In detail, the viscosity change rate is ±20% or less before and after storage for 30 minutes in the presence of a fluorescent lamp and in an air atmosphere at a temperature of 23°C.
[0013] Since the viscosity change rate of the active energy ray-curable composition 10 is ±20% or less, when spray coating is performed, the uncoated matter that does not adhere to the substrate 20 can be collected and the collected uncoated matter can be reused in spray coating as is. In other words, the recyclability of the active energy ray-curable composition that has become the uncoated matter is improved, and waste can be reduced.
[0014] The polyfunctional acrylate is a hydrophobic material having high reactivity. Since the polyfunctional acrylate has high reactivity, the curing speed of the active energy ray curable composition 10 can be increased by using the polyfunctional acrylate as the main component of the active energy ray curable composition 10.
[0015] Since the polyfunctional acrylate is hydrophobic, it can improve the adhesion between the active energy ray curable composition 10 and the substrate 20 when applied to a hydrophobic substrate. Therefore, it is possible to suppress peeling of the cured film from the substrate. In addition, since the adhesion between the cured film and the substrate is high, it is also possible to suppress the occurrence of cracks in a low temperature environment. Therefore, it is possible to form a cured film with excellent durability on the substrate.
[0016] The content of the polyfunctional acrylate is 90% by mass or more based on the total amount of the active energy ray-curable composition 10. In other words, the main component of the active energy ray-curable composition 10 is the polyfunctional acrylate.
[0017] Examples of polyfunctional acrylates that can be used include trimethylolpropane trimethacrylate, PEG200 diacrylate, PEG600 diacrylate, triethylene glycol diacrylate, pentaerythritol triacrylate, 2-hydroxy-3-acryloyloxypropyl acrylate, polytetramethylene glycol diacrylate, dipentaerythritol hexaacrylate, pentaerythritol triacrylate, etc. These polyfunctional acrylates may be used alone or in combination of two or more.
[0018] By using these polyfunctional acrylates as the main component of the active energy ray-curable composition 10, the viscosity of the active energy ray-curable composition can be adjusted to 10 to 60 mPa·s, which is a viscosity suitable for spray coating. It is more preferable to use PEG200 diacrylate, triethylene glycol diacrylate, polytetramethylene glycol diacrylate, or the like as the polyfunctional acrylate to adjust the viscosity of the active energy ray-curable composition to 10 to 30 mPa·s.
[0019] The initiator is a radical generator that generates highly active radicals when irradiated with ultraviolet light. These radical species undergo decomposition and react with resin components such as monomers and / or oligomers. This reaction product further reacts with another resin component, causing a chain reaction to proceed. Then, the crosslinking reaction proceeds, increasing the molecular weight, curing the multifunctional acrylate, and forming a cured film.
[0020] The content of the initiator is preferably 1% by mass or more and less than 10% by mass with respect to the total amount of the active energy ray curable composition 10. When the content of the initiator is less than 1% by mass, the curing of the active energy ray curable composition becomes insufficient, resulting in curing failure. On the other hand, when the content of the initiator is 10% by mass or more, the molecular weight does not increase, resulting in insufficient strength of the cured film.
[0021] As the initiator, an intramolecular cleavage type initiator such as 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, 4'-(2-hydroxyethoxy)-2-hydroxy-2-methylpropiophenone, 2-methyl-4'-(methylthio)-2-morpholinopropiophenone, etc. can be used. These initiators may be used alone or in combination of two or more.
[0022] In addition to the initiator, the active energy ray-curable composition 10 may contain various additives such as antibacterial agents, antifungal agents, antifoaming agents, antioxidants, antistatic agents, dyes, and polymerization inhibitors.
[0023] Examples of antibacterial agents include captan, carbendazim, quinomethionate, chlorothalonil, clozolinate, cyprodinil, epoxiconazole, famoxadone, fenarimol, fenbuconazole, fenfuram, fenpiclonil, azoxystrobin, benalaxyl, benomyl, bitertanol, fluazinam, fludioxonil, fluorimide, fluquinconazole, flusulfamide, flutolanil, folpet, Hexachlorobenzene, hexaconazole, ipoconazole, iprodione, kresoxim methyl, manzeb, maneb, mepanipyrim, mepronil, metconazole, metiram, phthalide, procymidone, propineb, quintozene, tecnazene, thifluzamide, thiophenate methyl, thiram, tolclofos methyl, tolylfluanid, triadimefon, triadimenol, triazoxide, triforine, etc. can be used. Inorganic antibacterial agents can also be used, for example, silver, copper, zinc, tin, lead, gold, etc. Furthermore, synthetic antibacterial agents can also be used, for example, polyhexamethylene hyguanide, hydrochloride, benzethonium chloride, alkyl polyaminoethyl glycine, benzisothiazoline, etc.
[0024] As the mildewproofing agent, for example, sodium dehydroacetate, sodium benzoate, sodium pyridinethione-1-oxide, p-hydroxybenzoic acid ethyl ester, 1,2-benzisothiazolin-3-one and salts thereof can be used.
[0025] Examples of the defoaming agent that can be used include fatty acid salts, liquid fatty oil sulfates, higher alcohol sulfates, fatty alcohol phosphates, fatty acid amide sulfonates, sulfonates of dibasic fatty acid esters, alkylarylsulfonates, polyoxyethylene alkyl ethers, polyoxyethylene alkylphenol ethers, polyoxyethylene alkyl esters, sorbitan alkyl esters, polyoxyethylene sorbitan alkyl esters, acrylic polymers, vinyl polymers, and organopolysiloxanes.
[0026] As the antioxidant, for example, a phenol-based antioxidant, a phosphorus-based antioxidant, a sulfur-based antioxidant, etc. can be used. As the phenol-based antioxidant, for example, 2,6-di-tert-butyl-p-cresol, stearyl β-(3',5'-di-tert-butyl-4-hydroxyphenyl)propionate, 1,3,5-trimethyl-2,4,6-tris(3',5'-di-tert-butyl-4-hydroxybenzyl)benzene, etc. can be used. As the phosphorus-based antioxidant, for example, tris(2,4-di-tert-butylphenyl)phosphite, diphenyl mono(2-ethylhexyl)phosphite, 2,2'-methylenebis(4,6-di-tert-butylphenyl)-2-ethylhexylphosphite, distearyl pentaerythritol diphosphite, tri(mononylphenyl)phosphite, etc. can be used. As the sulfur-based antioxidant, for example, dilauryl-3,3'-thiodipropionate, pentaerythritol tetrakis(3-laurylthiopropionate), etc. can be used.
[0027] Examples of the antistatic agent that can be used include various cationic antistatic agents having cationic groups such as primary to tertiary amino groups, quaternary ammonium salts, and pyridinium salts; anionic antistatic agents having anionic groups such as sulfonate groups, sulfate groups, phosphate groups, and phosphonate groups; amphoteric antistatic agents such as amino acid-based and amino sulfate-based; nonionic antistatic agents such as amino alcohol-based, glycerin-based, and polyethylene glycol-based; and polymeric antistatic agents obtained by increasing the molecular weight of the above-mentioned antistatic agents.
[0028] Examples of dyes that can be used include pyrazole azo compounds, anilino azo compounds, triarylmethane compounds, anthraquinone compounds, anthrapyridone compounds, benzylidene compounds, oxonol compounds, pyrazolotriazole azo compounds, pyridone azo compounds, cyanine compounds, phenothiazine compounds, pyrrolopyrazole azomethine compounds, xanthene compounds, phthalocyanine compounds, benzopyran compounds, indigo compounds, and pyrromethene compounds.
[0029] A polymerization inhibitor may be added to prevent the double bond from reacting. Examples of the polymerization inhibitor include hydroquinone (HQ), hydroquinone monomethyl ether (MEHQ), 2,6-di-t-butyl-4-methylphenol (BHT), t-butylcatechol (TBC), and phenol or naphthol derivatives such as 4-methoxy-1-naphthol, phenothiazine derivatives, and nitrosamine salts.
[0030] A method for producing a resin molded body 30 in which an active energy ray curable composition 10 is cured on the surface of a substrate 20 will be described with reference to FIG. 2. First, the active energy ray curable composition 10 is loaded into a paint gun (S1). Then, the substrate 20 to be coated is fixed to a coating jig (S2). The active energy ray curable composition 10 is applied to the surface of the substrate 20 with a paint gun so as to have a uniform film thickness of less than 10 μm (S3). The active energy ray curable composition 10 is irradiated with ultraviolet rays (S4). The active energy ray curable composition 10 is cured on the surface of the substrate 20 to form a cured film (S5). As described above, a resin molded body 30 in which the active energy ray curable composition 10 is cured on the surface of the substrate 20 can be produced.
[0031] When applying the active energy ray-curable composition 10 to the surface of the substrate 20, the composition may be applied to a part of the surface of the substrate 20, or may be applied to the entire surface of the substrate 20. The method of applying the active energy ray-curable composition 10 is not limited to a coating gun, and an application method using an inkjet or a dispenser may also be used.
[0032] The substrate 20 may be made of a hydrophobic synthetic resin such as polymethyl methacrylate resin (PMMA) or a hydrophobic material such as glass, in addition to polycarbonate resin (PC).
[0033] The active energy ray-curable composition 10 can be used as a hard coat or an anti-fog coat. The resin molded body 30 obtained by curing the active energy ray-curable composition 10 on the surface of the substrate 20 can be used as an outer lens (translucent cover) of a vehicle lamp, a window glass, a lens of glasses, a cover for the surface of an optical sensor, and the like. EXAMPLES
[0034] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.
[0035] Example 1 In a 300 mL separable flask equipped with a stirring blade, 95 parts by mass of trimethylolpropane trimethacrylate (product name: product code: T0912, manufactured by Tokyo Chemical Industry Co., Ltd.) was added as a multifunctional acrylate. Next, 5 parts by mass of 1-hydroxycyclohexyl phenyl ketone (product name: Omnirad184, manufactured by Sanyo Trading Co., Ltd.) was added as an initiator. This was stirred at room temperature for 30 minutes to obtain 100 parts by mass of the active energy ray curable composition of Example 1.
[0036] Example 2 In a 300 mL separable flask equipped with a stirring blade, 99 parts by mass of PEG200 diacrylate (product name: PEG200DA, manufactured by Daicel Allnex Corporation) was added as a multifunctional acrylate. Next, 1 part by mass of 1-hydroxycyclohexyl phenyl ketone (product name: Omnirad184, manufactured by Sanyo Trading Co., Ltd.) was added as an initiator. This was stirred at room temperature for 30 minutes to obtain 100 parts by mass of the active energy ray curable composition of Example 2.
[0037] Example 3 In a 300 mL separable flask equipped with a stirring blade, 90 parts by mass of PEG600 diacrylate (product name: EBECRYL 11, manufactured by Daicel-Allnex Corporation) was added as a multifunctional acrylate. Next, 10 parts by mass of 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methylpropane (product name: Omnirad2959, manufactured by Sanyo Trading Co., Ltd.) was added as an initiator. This was stirred at room temperature for 30 minutes to obtain 100 parts by mass of the active energy ray curable composition of Example 3.
[0038] Example 4 In a 300 mL separable flask equipped with a stirring blade, 95 parts by mass of triethylene glycol diacrylate (product name: Light Acrylate 3EG-A, manufactured by Kyoeisha Chemical Co., Ltd.) was added as a multifunctional acrylate. Next, 5 parts by mass of 1-hydroxycyclohexyl phenyl ketone (product name: Omnirad184, manufactured by Sanyo Trading Co., Ltd.) was added as an initiator. This was stirred at room temperature for 30 minutes to obtain 100 parts by mass of the active energy ray curable composition of Example 4.
[0039] Example 5 In a 300 mL separable flask equipped with a stirring blade, 95 parts by mass of triethylene glycol diacrylate (product name: Light Acrylate 3EG-A, manufactured by Kyoeisha Chemical Co., Ltd.) was added as a multifunctional acrylate. Next, 5 parts by mass of 4'-(2-hydroxyethoxy)-2-hydroxy-2-methylpropiophenone (product name: Omnirad2959, manufactured by Sanyo Trading Co., Ltd.) was added as an initiator. This was stirred at room temperature for 30 minutes to obtain 100 parts by mass of the active energy ray curable composition of Example 5.
[0040] Example 6 In a 300 mL separable flask equipped with a stirring blade, 13 parts by mass of pentaerythritol triacrylate (product name: Light Acrylate PE-3A, manufactured by Kyoeisha Chemical Co., Ltd.) and 85 parts by mass of PEG200 diacrylate (product name: PEG200DA, manufactured by Daicel-Allnex Corporation) were added as a multifunctional acrylate. Next, 2 parts by mass of 1-hydroxycyclohexyl phenyl ketone (product name: Omnirad184, manufactured by Sanyo Trading Co., Ltd.) were added as an initiator. This was stirred at room temperature for 30 minutes to obtain 100 parts by mass of the active energy ray curable composition of Example 6.
[0041] Example 7 In a 300 mL separable flask equipped with a stirring blade, 50 parts by mass of 2-hydroxy-3-acryloyloxypropyl acrylate (product name: Light Ester G-201P, manufactured by Kyoeisha Chemical Co., Ltd.) and 45 parts by mass of triethylene glycol diacrylate (product name: Light Acrylate 3EG-A, manufactured by Kyoeisha Chemical Co., Ltd.) were added as a multifunctional acrylate. Next, 5 parts by mass of 2-methyl-4'-(methylthio)-2-morpholinopropiophenone (product name: Omnirad907, manufactured by Sanyo Trading Co., Ltd.) were added as an initiator. This was stirred at room temperature for 30 minutes to obtain 100 parts by mass of the active energy ray curable composition of Example 7.
[0042] Example 8 In a 300 mL separable flask equipped with a stirring blade, 60 parts by mass of 2-hydroxy-3-acryloyloxypropyl acrylate (product name: Light Ester G-201P, manufactured by Kyoeisha Chemical Co., Ltd.) as a multifunctional acrylate and 35 parts by mass of polytetramethylene glycol diacrylate (product name: Light Acrylate PTMGA-250, manufactured by Kyoeisha Chemical Co., Ltd.) were added. Next, 5 parts by mass of 1-hydroxycyclohexyl phenyl ketone (product name: Omnirad184, manufactured by Sanyo Trading Co., Ltd.) were added as an initiator. This was stirred at room temperature for 30 minutes to obtain 100 parts by mass of the active energy ray curable composition of Example 8.
[0043] Example 9 In a 300 mL separable flask equipped with a stirring blade, 97 parts by mass of polytetramethylene glycol diacrylate (product name: Light Acrylate PTMGA-250, manufactured by Kyoeisha Chemical Co., Ltd.) was added as a multifunctional acrylate. Next, 3 parts by mass of 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methylpropane (product name: Omnirad2959, manufactured by Sanyo Trading Co., Ltd.) was added as an initiator. This was stirred at room temperature for 30 minutes to obtain 100 parts by mass of the active energy ray curable composition of Example 9.
[0044] Example 10 In a 300 mL separable flask equipped with a stirring blade, 15 parts by mass of dipentaerythritol hexaacrylate (product name: Light Acrylate DPE-6A, manufactured by Kyoeisha Chemical Co., Ltd.) and 80 parts by mass of polytetramethylene glycol diacrylate (product name: Light Acrylate PTMGA-250, manufactured by Kyoeisha Chemical Co., Ltd.) were added as a multifunctional acrylate. Next, 5 parts by mass of 1-hydroxycyclohexyl phenyl ketone (product name: Omnirad184, manufactured by Sanyo Trading Co., Ltd.) were added as an initiator. This was stirred at room temperature for 30 minutes to obtain 100 parts by mass of the active energy ray curable composition of Example 10.
[0045] Example 11 In a 300 mL separable flask equipped with a stirring blade, 15 parts by mass of pentaerythritol triacrylate (product name: Light Acrylate PE-3A, manufactured by Kyoeisha Chemical Co., Ltd.) and 80 parts by mass of triethylene glycol diacrylate (product name: Light Acrylate 3EG-A, manufactured by Kyoeisha Chemical Co., Ltd.) were added as a multifunctional acrylate. Next, 5 parts by mass of 1-hydroxycyclohexyl phenyl ketone (product name: Omnirad184, manufactured by Sanyo Trading Co., Ltd.) were added as an initiator. This was stirred at room temperature for 30 minutes to obtain 100 parts by mass of the active energy ray curable composition of Example 11.
[0046] Comparative Example 1 In a 300 mL separable flask equipped with a stirring blade, 95 parts by mass of pentaerythritol tetraacrylate (product name: Light Acrylate PE-4A, manufactured by Kyoeisha Chemical Co., Ltd.) was added as a multifunctional acrylate. Next, 5 parts by mass of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (product name: Omnirad TPO, manufactured by Sanyo Trading Co., Ltd.) was added as an initiator. This was stirred at room temperature for 30 minutes to obtain 100 parts by mass of the active energy ray curable composition of Comparative Example 1.
[0047] (Viscosity measurement) The first viscosity was measured for each of the active energy ray-curable compositions of Examples 1 to 11 and the active energy ray-curable composition of Comparative Example 1. The viscosity was measured using an E-type viscometer (product name: TVE-22L, manufactured by Toki Sangyo Co., Ltd.) in accordance with JIS K2283. The viscosity measurement results of Examples 1 to 11 and Comparative Example 1 are shown together in FIG.
[0048] (Measurement of viscosity change) The active energy ray curable compositions of Examples 1 to 11 or the active energy ray curable composition of Comparative Example 1 were spray-coated (Anest Iwata, gravity spray coating, W-50-124BPG) on a substrate to a film thickness of 10 μm, and the uncoated parts that did not adhere to the surface of the substrate were collected by receiving them in a stainless steel tray at a 45-degree inclination on a PTFE sheet, and then transferred to a Good Boy (sealed container) and covered. After leaving this at a temperature of 23° C. under a fluorescent lamp for 30 minutes, the second viscosity was measured for each. The viscosity was measured using an E-type viscometer (product name: TVE-22L, manufactured by Toki Sangyo Co., Ltd.) in accordance with JIS K2283. FIG. 3 shows the measurement results of the viscosity change in Examples 1 to 11 and Comparative Example 1.
[0049] (Evaluation of viscosity change rate) The viscosity change rate was calculated by substituting the first viscosity and the second viscosity into the following formula 1, and the viscosity change rate of the active energy ray-curable compositions of Examples 1 to 11 and the active energy ray-curable composition of Comparative Example 1 was evaluated. Viscosity change rate (%) = (second viscosity - first viscosity) ÷ first viscosity x 100 The evaluation was made as follows: when the viscosity change rate was 0% or more and less than 5%, it was rated as A, when the viscosity change rate was 5% or more and less than 10%, it was rated as B, when the viscosity change rate was 10% or more and less than 15%, it was rated as C, when the viscosity change rate was 15% or more and less than 20%, it was rated as D, and when the viscosity change rate was 20% or more, it was rated as E. The evaluation results of the viscosity change rates of Examples 1 to 11 and Comparative Example 1 are collectively shown in Fig. 3.
[0050] (Evaluation of content of non-reactive volatile organic solvents) The active energy ray curable compositions of Examples 1 to 11 and the active energy ray curable composition of Comparative Example 1 were each subjected to gas chromatography analysis at 200°C, and the total value of components detected in structures not containing vinyl groups or acryloyl groups was determined. The evaluation was as follows: if the total value was less than 1 mass%, A; if the total value was 1 mass% or more and less than 10 mass%, B; if the total value was 10 mass% or more and less than 30 mass%, C; if the total value was 30 mass% or more and less than 50 mass%, D; and if the total value was 50 mass% or more, E. FIG. 3 shows the evaluation results of the content of non-reactive volatile organic solvents of Examples 1 to 11 and Comparative Example 1.
[0051] (Evaluation of ejection properties) The viscosity of the active energy ray-curable compositions of Examples 1 to 11 or the active energy ray-curable composition of Comparative Example 1 was evaluated from the first viscosity. The evaluation was as follows: when the viscosity was 3 mPa·s or more and less than 30 mPa·s, it was rated A; when the viscosity was 30 mPa·s or more and less than 40 mPa·s, it was rated B; when the viscosity was 40 mPa·s or more and less than 50 mPa·s, it was rated C; when the viscosity was 50 mPa·s or more and less than 80 mPa·s, it was rated D; and when the viscosity was 80 mPa·s or more, it was rated E. The evaluation results of the dischargeability of Examples 1 to 11 and Comparative Example 1 are shown together in FIG. 3.
[0052] As is clear from Fig. 3, the active energy ray-curable compositions of Examples 1 to 11 have lower viscosities and viscosity change rates than the comparative examples. Therefore, the active energy ray-curable compositions of Examples 1 to 11 are suitable for spray coating, and the active energy ray-curable compositions of Examples 1 to 11 that have become uncoated can be reused as paints.
[0053] In addition, it is clear that the active energy ray curable compositions of Examples 1 to 11 can reduce the content of non-reactive volatile organic solvents and ensure excellent dischargeability. Therefore, the ratio of the active ingredient that becomes the cured film is large, the total amount of materials can be reduced, and there is no need to dilute with an organic solvent when spray coating, which reduces power consumption during production.
[0054] From the results of Examples 1, 2, and 4 to 11, it is clear that when the content of the initiator is 5% or less, the second viscosity is 55 mPa s or less, and therefore the uncoated active energy ray-curable composition is suitable for reuse as a coating material.
[0055] From the results of Examples 2, 4, 5, 6, 9, and 11, it is clear that when PEG200 diacrylate, triethylene glycol diacrylate, or polytetramethylene glycol diacrylate is contained as the main component as the multifunctional acrylate, the viscosity was less than 40 mPa s in the ejection property evaluation, which shows that better ejection property can be imparted.
[0056] In contrast, the active energy ray-curable composition of Comparative Example 1 has a high viscosity change rate, so that the uncoated active energy ray-curable composition cannot be reused as a paint. Also, in the evaluation of the dischargeability, the viscosity is 80 mPa s or more, so it is clear that spray coating is not possible unless it is diluted with an organic solvent.
[0057] As described above, according to the present invention, it is possible to provide a reusable active energy ray-curable composition 10 and a resin molded article 30 having a cured film obtained by curing the active energy ray-curable composition 10. [Explanation of symbols]
[0058] 10. Active energy ray curable composition 20 Base material 30 Resin molding
Claims
1. A solventless active energy ray curable composition comprising a multifunctional acrylate and an intramolecular cleavage initiator, The active energy ray-curable composition has a viscosity of 10 to 60 mPa·s, and a viscosity change rate before and after storage for 30 minutes in the presence of a fluorescent lamp and in an air atmosphere at a temperature of 23° C. is ±20% or less.
2. 2. The active energy ray-curable composition according to claim 1, having a viscosity of 10 to 30 mPa·s.
3. A cured film obtained by curing the active energy ray-curable composition according to claim 1 or 2; and a substrate having the cured film on at least a portion of its surface.
4. 4. The resin molded article according to claim 3, wherein the substrate is hydrophobic.
5. 5. The resin molded article according to claim 4, wherein the substrate is a polymethyl methacrylate resin or a polycarbonate resin.
6. 4. The resin molding according to claim 3, which is an outer lens of a vehicle lamp.
Citation Information
Patent Citations
Recovery method and recovery apparatus for UV-curable coating
JP2005342550A